KRISTAL HEMOGLOBIN PADA BERCAK DARAH YANG TERPAPAR BEBERAPA SABUN MANDI PADAT NON ANTISEPTIK DENGAN TES TEICHMANN DAN TES TAKAYAMA - Fika Maulidah; Enikarmila Asni; Mohammad Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBloodstains found on crime scene usually cleaned and camouflaged by the criminals as an attempt to eliminate the evidence. One of the way to eliminate the evidence is by using non antiseptic bar soap that can be found easily on the market. The contamination of non antiseptic bar soap on the bloodstains could probably influence the result of bloodstain’s identification by Teichmann test and Takayama test. This study was conducted to describe the crystal formation of hemoglobin at bloodstains that exposed with some brand of non antiseptic bar soap by Teichmann test and Takayama test. Each of bloodstain’s sample were exposed by flowing the non antiseptic bar soap that has been smoothed and dissolved in water. There were 66 samples that observed and found positive results on all samples (100%) through Teichmann test and Takayama test. These results showed that hemoglobin crystals still could be found even after the bloodstains were exposed by non antiseptic bar soap. The conclusion of this research is non antiseptic bar soaps do not influence the formation of hemoglobin crystals.Keyword : hemoglobin crystals, bloodstain, Teichmann test , Takayama test, non antiseptic bar soap